Rút gọn: (a-2b)^2 + 8ab ; ta được: A. a^2-4b^2 B. (a-2b)^2 C. a^2+4b^2 D. (a+2b)^2

Rút gọn: (a-2b)^2 + 8ab ; ta được:
A. a^2-4b^2
B. (a-2b)^2
C. a^2+4b^2
D. (a+2b)^2

2 bình luận về “Rút gọn: (a-2b)^2 + 8ab ; ta được: A. a^2-4b^2 B. (a-2b)^2 C. a^2+4b^2 D. (a+2b)^2”

  1. Giải đáp + Lời giải và giải thích chi tiết:
    ( a – 2b )^2 + 8ab
    = [ a^2 – 2 . a . 2b + ( 2b )^2 ] + 8ab
    = ( a^2 – 4ab + 4b^2 ) + 8ab
    = a^2 – 4ab + 4b^2 + 8ab
    = a^2 + 4b^2 + 4ab
    = ( a^2 + 4ab + 4b^2 )
    = [ a^2 + 2 . a . 2b + ( 2b )^2 ]
    = ( a + 2b )^2
    ⇒ Chọn đáp án D
    #tn

    Trả lời
  2. Giải đáp + Lời giải và giải thích chi tiết:
    Ta có:(a-2b)^2 + 8ab
    =a^2 – 4ab + 4b^2 + 8ab
    =a^2 + 4ab + 4b^2
    =(a + 2b)^2
    Chọn bb D

    Trả lời

Viết một bình luận

Câu hỏi mới